Postoperative Complications Following Pharyngolaryngectomy With Total Esophagectomy: Comparison Between Cervical and Anterior Mediastinal Tracheostomy. (July 2023) - Kanie, Yasukazu; Okamura, Akihiko; Kanamori, Jun; Imamura, Yu; Kamiyama, Ryosuke; Seto, Akira; Shimbashi, Wataru; Sasaki, Toru; Fukushima, Hirofumi; Mitani, Hiroki; Watanabe, Masayuki
Objectives: Pharyngolaryngectomy with total esophagectomy (PLTE) is associated with high morbidity and mortality rates. Cervical tracheostomy (CT) is the first choice of tracheostomy, whereas anterior mediastinal tracheostomy (AMT) is sometimes required due to tumor extension or insufficient blood supply to the tracheal tip. However, the differences in the outcomes between CT and AMT after PLTE remain unclear. Methods: We retrospectively reviewed 67 patients who underwent PLTE and compared the clinical features and postoperative complications between patients with CT and AMT. The characteristics and the outcomes were compared between the groups stratified by the causes of AMT. Results: Of the 67 patients, 42 (62.7%) patients underwent PLTE with CT (CT group), whereas 25 (37.3%) underwent PLTE with AMT (AMT group). The AMT group included more cervicothoracic esophageal cancers and had showed an advanced T stage compared to the CT group ( P  < .01 and .01, respectively). The incidences of pneumonia and surgical site infection (SSI) were more frequent in the AMT group than in the CT group ( P  = .03 and .01, respectively). Surgery-related mortality was only observed in the AMT group. In the AMT group, 17 (68.0%) and 8 (32.0%) patients underwent AMT because of tumor extension and insufficient supply to the tracheal tip. The latter cases underwent transthoracic esophagectomy more frequently than former cases ( P  = .03). Conclusion: AMT after PLTE had more postoperative complications and mortality than CT. In cases that may need AMT, a transhiatal approach is preferable over transthoracic esophagectomy to avoid fatal complications when oncologically permissive.